Characterization of mutant mitochondrial plasmids of Neurospora spp. that have incorporated tRNAs by reverse transcription. - Akins, R A (1989)
The Mauriceville and Varkud mitochondrial plasmids of Neurospora spp. are closely related, closed-circular DNAs (3.6 and 3.7 kilobases, respectively) whose nucleotide sequences and genetic organization suggest relationships to mitochondrial introns and retroelements. We have characterized nine suppressive mutants of these plasmids that outcompete mitochondrial DNA and lead to impaired growth. All nine suppressive plasmids contain small insertions, corresponding to or including a mitochondrial tRNA (tRNATrp, tRNAGly, or tRNAVal) or a tRNA-like sequence. The insertions are located at the position corresponding to the 5' end of the major plasmid transcript or 24 nucleotides downstream near a cognate of the sequence at the major 5' RNA end. The structure of the suppressive plasmids suggests that the tRNAs were inserted via an RNA intermediate. The 3' end of the wild-type plasmid transcript can itself be folded into a secondary structure which has tRNA-like characteristics, similar to the tRNA-like structures at the 3' ends of plant viral RNAs. This structure may play a role in replication of the plasmids by reverse transcription. Major transcripts of the suppressive plasmids begin at the 5' end of the inserted mitochondrial tRNA sequence and are present in 25- to 100-fold-higher concentrations than are transcripts of wild-type plasmids. Mapping of 5' RNA ends within the inserted mtDNA sequences identifies a short consensus sequence (PuNPuAG) which is present at the 5' ends of a subset of mitochondrial tRNA genes. This sequence, together with sequences immediately upstream in the plasmids, forms a longer consensus sequence, which is similar to sequences at transcription initiation sites in Neurospora mitochondrial DNA. The suppressive behavior of the plasmids is likely to be directly related to the insertion of tRNAs leading to overproduction of plasmid transcripts.